2006
DOI: 10.1007/s00441-006-0217-1
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix and synapses

Abstract: Extracellular matrix (ECM) molecules, derived from both neurons and glial cells, are secreted and accumulate in the extracellular space to regulate various aspects of pre- and postsynaptic differentiation, the maturation of synapses, and their plasticity. The emerging mechanisms comprise interactions of agrin, integrin ligands, and reelin, with their cognate cell-surface receptors being coupled to tyrosine kinase activities. These may induce the clustering of postsynaptic receptors and changes in their composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
90
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 50 publications
2
90
0
1
Order By: Relevance
“…Although this fraction of GABAergic interneurons in the cortex is relatively constant from neurogenesis to adulthood [30], during postnatal development a subgroup of these cells expressing the Ca ++ -binding protein parvalbumin gradually accumulate extracellular matrix components around the cell body, such as chondroitin sulfate proteoglycans, forming a lattice-like structure called perineuronal net (PNN). PNNs mature slowly and help stabilize synaptic contacts under environmental constraints [31][32][33][34][35]. Their maturation signals the closing of the critical period of plasticity in several cortical regions [31,32,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Although this fraction of GABAergic interneurons in the cortex is relatively constant from neurogenesis to adulthood [30], during postnatal development a subgroup of these cells expressing the Ca ++ -binding protein parvalbumin gradually accumulate extracellular matrix components around the cell body, such as chondroitin sulfate proteoglycans, forming a lattice-like structure called perineuronal net (PNN). PNNs mature slowly and help stabilize synaptic contacts under environmental constraints [31][32][33][34][35]. Their maturation signals the closing of the critical period of plasticity in several cortical regions [31,32,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…ECM represents a molecular net that surrounds brain cells and might occupy up to 20% of the brain volume [1]. ECM molecules are produced by the Golgi apparatus in neurons and glial cells [1][2][3][4]. ECM molecules play an important role during the development and in the adult brain in normal and pathological conditions, including regeneration processes [4][5][6][7][8].…”
Section: Introduction the Brain Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…Furthermore, it had been shown that CSPGs accumulate in the Ranvier nodes of myelinated axons, which adjusts the ionic conductivity of the fibre by creating an ion barrier [47]. Also glycosaminoglycan chains can bind to neural cell adhesion molecules (NCAM) and polysialic acid through a fibroblast growth factor (FGF) on presynaptic terminal, increasing ECM accumulation and its signaling in presynapse [3].…”
Section: Introduction the Brain Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…Furthermore, it has been shown the ECM and osteogenic protein-1 play an important role on the morphological differentiation of rat sympathetic neurons (Lein et al, 1996). Glial cells have long been recognized as participating in development of neural tissue by providing a scaffolding for migration and by synthesis and secretion of a variety of growth factors and ECM components (Sobeih and Corfas, 2002;Dityatev and Schachner, 2006). An additional role for glia and other non-neuronal cells in the electrical differentiation of neurons has been suggested by several articles, in particular a group that has focused on the potassium currents that influence AP repolarization and repetitive activity (Barish, 1995).…”
Section: Introductionmentioning
confidence: 99%